2012
DOI: 10.5120/7945-1282
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Algorithm for Layout Analysis of Arabic Document Images and Text Lines Extraction

Abstract: Text and not-text segmentation and text line extraction from document images are the most challenging problems of information indexing of Arabic document images such as books, technical articles, business letters and faxes in order to successfully process them in systems such as OCR. Researches on Arabic language related to documents digitization have been focusing on word and handwriting recognition. Few approaches have been proposed for layout analysis for Arabic scanned/captured documents. In this paper we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Elanwar et al [16,20,23] proposed various analyses based on SVM (support vector machine) classifiers for extracting six logical labels from book pages. The same classifier was utilized by Alshameri et al [19] and Hesham et al [13,22] for text and non-text segmentation. Another learning technique used for segmentation and classification is neural network classification (Multilayer Perceptron-Back propagation) [9], whereas Ahmed et al [10] used k-means clustering and Gaussian Mixture Modelling (GMM).…”
Section: Arabic Document Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elanwar et al [16,20,23] proposed various analyses based on SVM (support vector machine) classifiers for extracting six logical labels from book pages. The same classifier was utilized by Alshameri et al [19] and Hesham et al [13,22] for text and non-text segmentation. Another learning technique used for segmentation and classification is neural network classification (Multilayer Perceptron-Back propagation) [9], whereas Ahmed et al [10] used k-means clustering and Gaussian Mixture Modelling (GMM).…”
Section: Arabic Document Analysis Methodsmentioning
confidence: 99%
“…Many studies successfully select the best binarization method relative to the benchmarking dataset's category. Several studies [11][12][13]22] have confirmed the efficiency of adaptive thresholding [35], such as Otsu thresholding [26] and Sauvola thresholding [27], whereas other studies [7,12,19] used filters for denoising, such as median filters [31] and Gaussian filters. The noise is presented as marginal noise, background noise, edge noise, rule line noise, pattern noise, and salt and pepper noise that can be created during scanning, transmission, or conversion to digital form, which affects the analysis process.…”
Section: A Preprocessing Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The dataset provided by Bukhari et al [5] contains 25 images from books and newspapers, including multi-script images that contain both English and Arabic script; the Hadjar and Ingold datasets [11,12,13] contain between 50 to 150 pages from three different newspapers (Annahar, AL Hayat, and AL Quds), and the dataset by ElShameri et al [3] contains 200 pages from newspapers. The database by the Environmental Research Institute of Michigan [26] consists of 750 images of pages from machine-printed Arabic books and magazines.…”
Section: Existing Benchmarks For Dla Research Are Smallmentioning
confidence: 99%
“…• Alshameri et al in [4] presented a method for text/non-text segmentation and text line extraction from document images, where they used RLSA, CCs for text segmentation and an SVM for figure detection, by applying the ANDing and ORing operations to set the correct bounding-box for each category (text/figure). This technique gave interesting results, but the application of their RLSA is efficient only in certain special cases, where specific thresholds have to be applied, and specific vertical/horizontal projections are used to distinguish between CCs with a special spatial structure.…”
Section: Smartphone-captured Arabic Newspaper Analysismentioning
confidence: 99%